Atomistic Study on Size Effects in Thermally Induced Martensitic Phase Transformation of NiTi. (11th October 2016) - Gur, Sourav; Frantziskonis, George N.
Abstract : The atomistic study shows strong size effects in thermally induced martensitic phase transformation evolution kinetics of equiatomic NiTi shape memory alloys (SMAs). It is shown that size effects are closely related to the presence of free surfaces; thus, NiTi thin films and nanopillars are studied. Quasi-static molecular dynamics simulations for several cell sizes at various (constant) temperatures are performed by employing well-established interatomic potentials for NiTi. The study shows that size plays a crucial role in the evolution of martensite phase fraction and, importantly, can significantly change the phase transformation temperatures, which can be used for the design of NiTi based sensors, actuators, or devices at nano- to microscales. Interestingly, it is found that, at the nanometer scale, Richard's equation describes very well the martensite phase fraction evolution in NiTi thin films and nanopillars as a function of temperature.